Ganoderma Diversity and Its Interactions with Hosts and Neighbouring Insects in Gunung Walat Educational Forest - Mayra, Mahreza Tadsa; Chan, Carey; Abdurrahman, Naufal Hafiz; Putra, Ivan Permana (UIN Sunan Gunung Djati Bandung, 2024)
Ganoderma spp. is a genus of macrofungi in the Basidiomycota, comprising both saprophytic and phytopathogenic species. Ganoderma spp. prefers woody substrates and can attack various trees in the forest. While it often acts as a phytopathogenic fungus, it also serves an ecological role for surrounding insects, providing food and shelter. This study aims to determine the interactions and preferences of Ganoderma spp. with its hosts and to observe the interactions between Ganoderma spp. and surrounding insects. Research on these interactions was conducted through scan sampling exploration in the Gunung Walat Educational Forest. Identification of fungi, trees, and insects was based on morphological characteristics. A total of 155 fruiting bodies of Ganoderma were found. Three species of Ganoderma were successfully collected and described morphologically, both macroscopically and microscopically. Ganoderma spp. were found infecting Agathis sp., Schima wallichii, and Pinus merkusii trees. The fruiting bodies of Ganoderma spp. interacted with insects such as larvae, Trichomyrmex destructor ants, and Eumorphus marginatus beetles, which used the fruiting bodies as breeding and shelter sites